TINJAUAN ATAS PENGELOLAAN DANA DESA PADA KANTOR DESA SARIWANGI KECAMATAN PARONGPONG - Bokings, Tri Pratiwi Olivia Riska; Anwar, Sifaul; Nurochman, Mochamad Ilham (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2024)
The purpose of this study is this research was conducted to determine the extent and how the management of village funds in Sariwangi Village Office, Parongpong District. The method used in this study uses a descriptive method with a qualitative approach. The data collection technique of this research was done by observation, interviews, literature study, and documentation. The types and sources of data in this study are RKP Desa, reports on the realization of the implementation of the village income and expenditure budget. The results showed that the management of village funds at the Sariwangi Village Office was in accordance with Government Regulation No. 113 of 2014. It is hoped that the management of village funds in Sariwangi Village, Parongpong District, which is in accordance with Government Regulation No. 113 of 2014 can be maintained and become even better in the future.